Instagram Stories and Personal Branding Among Communication Students at Mercu Buana University - Nandira Adisty; Yanti, Nur Fitri (LPPM Stikosa - AWS, 2024)
This research aims to examine the influence of utilizing Instagram Stories on personal branding among students of the Faculty of Communication Sciences at Mercu Buana University in Jakarta. A quantitative approach with an explanatory survey method was employed in this study. The population consisted of active undergraduate students of the 2016 cohort in the Communication Studies program, with a sample of 171 respondents obtained through proportional stratified random sampling. Data were collected through a questionnaire using a Likert scale. Data analysis included descriptive statistics and simple linear regression analysis. The results indicate a positive and significant influence of Instagram Stories utilization on students' personal branding, with a regression coefficient of 0.900, a determination coefficient of 66.9%, and a t-value greater than the t-table value (18.334 > 1.65392). These findings confirm that Instagram Stories can potentially be utilized as a means to build effective personal branding for students through the posting of engaging content that reflects their personality and embraced values. However, it is important to note that personal branding is not solely influenced by the use of Instagram Stories but also by other factors such as consistency, audience interaction, and a profound understanding of personal branding strategies.